PENDAMPINGAN SOSIAL EMOSI ANAK BERMASALAH (JUVENILE DILIQUENCY) DI LPKA KELAS II A BANDA ACEH BERBASIS COMMUNITY BASED RESEARCH - Miftahul Jannah; Ismiati; Munawiah Abdullah; Nurul Azkia Salsabila (DEDICATION: Jurnal Pengabdian Masyarakat, 2024)
One of the issues today is juvenile deliquency, manifesting in actions outside of self-awareness and self-control, such as rape, murder, theft, and involvement in drug trafficking. The purpose of this research is to determine 1) the social-emotional condition of problematic children in Lembaga Pembinaan Khusus Anak Kelas II Banda Aceh (Special Child Rehabilitation Institution), and 2) the causes of deviant behavior in the social-emotion aspects of children in LPKA Class II Banda Aceh. The research method used is quantitative research with descriptive statistics and pre-experimental pretest-posttest and supported by in-depth interviews. Quantitative data analysis used One Way Anova with descriptive statistics and operated with SPSS 22 software, and supported by qualitative method. The instrument used in this research is the Social Emotio Character Development (SECD) with 28 statement items. The subjects are all children in LPKA Class II Banda Aceh, which is 22 individuals, all of whom are male. The results of the research show that the social-emotional values of children in LPKA have the low social-emotional level consists of 5 individuals (23%), the moderate level consists of 6 individuals (27%), and those with high social-emotional levels consist of 11 individuals (50%). Low social-emotional individuals are those with cases of theft and rape. From the interview results, it is found that the main factor causing deviant behavior in the social-emotional aspects of problematic children is the environment, as the primary factor influencing the social-emotional aspects of children in LPKA Class II Banda Aceh.